PERAN PENDIDIKAN KARAKTER DALAM MENUMBUHKAN SIKAP POSITIF SISWA SEKOLAH DASAR - Dwi Intan Maharani; Sahrun Nisa, Ari Suriani (ADISAM PUBLISHER, 2025)
Character education is an effort made by teachers or schools as an effort to instill character values, religion, morals, ethics, to students through science. The role of education in fostering positive attitudes in students requires an in-depth approach directly in order to know how the character of the students so that it can play a role in fostering positive attitudes to students and can improve the character of the younger generation and the nation. This article discusses the approach in the role of character education in fostering positive attitudes of elementary school students using the literature study research method. Literature study research is an analysis of relevant literature sources to understand these aspects. The data and information obtained from the sources are then analyzed and compiled in the form of comprehensive writing. The results of this article show that the need for the role of character education in fostering positive attitudes of elementary school students